Effects of nicotine on the human nasal mucosa. Issue 6 (June 1993) - Greiff, L; Wollmer, P; Erjefält, I; Andersson, M; Pipkorn, U; Persson, C G
Abstract : BACKGROUND–Topical application of nicotine and stimulation of tachykinin containing sensory nerves have been shown to produce mucosal exudation of plasma and derangement of the epithelial lining in guinea pig and rat airways. If this occurred in man these effects might contribute to the pathogenesis of airway disease. This study, performed in healthy volunteers without atopy, examined whether nicotine affects the plasma exudation response and the mucosal absorption permeability of the human nasal airway. METHODS–The acute effects of increasing topical doses of nicotine (0.08-2.0 mg) were examined (n = 8) on nasal symptoms (pain), mucosal exudation of plasma (albumin), mucosal secretion of mucin (fucose), and mucosal exudative responsiveness (histamine induced mucosal exudation of albumin). A separate placebo controlled study was carried out to determine whether frequent applications of the high dose of nicotine (2.0 mg given eight times daily for nine days) had any deleterious effects on the airway mucosa detectable as altered responses to histamine challenge. Both mucosal exudation of plasma (n = 12) and mucosal absorption of chromium-51 labelled EDTA (n = 8) were thus examined in nasal airways exposed to both nicotine and histamine. RESULTS–Nicotine caused nasal pain and produced dose dependent mucosal secretion of fucose but failed to produce any mucosal exudation of albumin. The exudative responsiveness to histamine was, indeed, decreased when the challenge was performed immediately after administration of acute doses of nicotine, whereas the responsiveness was unaffected when histamine challenges were carried out during prolonged treatment with nicotine. The nasal mucosal absorption of 51Cr-EDTA in the presence of histamine did not differ between subjects receiving either placebo or nicotine treatment for nine days. CONCLUSIONS–The results indicate that nicotine applied to the human airway mucosa produces pain and secretion of mucin, but inflammatory changes such as mucosal exudation of plasma and epithelial disruption may not be produced. Neurogenic inflammatory responses, which are so readily produced in guinea pig and rat airways, may not occur in human airways.